ULUL ALBAB DALAM TAFSIR FI ZHILAL AL-QUR’AN KITAB TAFSIR SAYYID QUTHB - M. Taib Hunsouw (IAIN Ambon, 2017)
One of the great Sayyid Qutb’s works is Tafsir Fi Zhilal al-Qur'an which has adabi patterns or literature and preaching. One verse that becomes the author concentration of his tafsir is the ulul albab verses meaning “the owner of the doors” or who has brain or mind that concentrate to Allah.